Rocky ford water power - Sanderson, Martin Wilbur (My University, 1898)
Introduction: The questions have often been asked, can the Blue River be used for irrigation purposes and, can this river be profitably used for power purposes? These questions have been investigated and the result of the investigation will be found in the following pages. Rocky Ford is situated on the Blue River, about four miles north of the city of Manhattan, Kansas, in, approximately, latitude 39 degrees 12 inches north, and longitude 96 degrees 35 inches west. It derives its name from the fact that at this place there is a smooth rock bottom running entirely across the river; which affords a first class foundation for a dam, mills, and other buildings. The river bank on the west side rises forty-five feet to the Blue Valley Railroad track, from which the ground gradually slopes back a quarter of a mile, where it terminates in a bluff, containing an immense amount of the best structural limestone. The east side of the river is a level plain from twenty to twenty-five feet above the rock bottom of the river.
Citation: Sanderson, Martin Wilbur. Rocky ford water power. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Blue River; Irrigatoin; Rocky Ford; Theses; Manuscripts (documents)